Prevalence and Type Distribution of Human Papillomavirus in Invasive Cervical Cancer in Aba, South-East Nigeria: A Sentinel Study to Encourage and Guide HPV Vaccination - Emmanuel, Akwuruoha; Chidi, Onwuka; Ndukauba, Eleweke; Chisara, Umezurike; Chuks, Kamanu; Chimdi, Eleweke (Asian Pacific Journal of Cancer Nursing, 2025)
Background: Despite the established link between human papillomavirus (HPV) and the pathogenesis of invasive cervical cancer and its precursor lesions, HPV vaccine acceptance faces cultural and religious biases in this region. There is no available local epidemiological study to support the current advocacy of HPV vaccination for the primary prevention of cervical cancer in this region. In this cross-sectional epidemiological study, we determined the prevalence and types of HPV in invasive cervical cancer so as to encourage and guide HPV vaccination for the primary prevention of cervical cancer in this south-east region of Nigeria. Methology: Two-hundred archived formalin-fixed, paraffin-embedded tissue blocks with confirmed diagnoses of invasive cervical cancer during the study period (2015-2024) were retrieved and examined. DNA was extracted by proteinase k lysis procedure while HPV DNA amplification, detection and typing was done using E7 type-specific multiplex genotyping (E7-MPG), which combines multiplex polymerase chain reaction (PCR) and hybridization to type-specific oligonucleotide probes on fluorescent beads. Result: Fourteen blocks were excluded from the analysis for inadequacy. A total of 79% (147/186) invasive cervical cancers were positive for single or multiple high-risk HPV types. HPV 16 was the predominant high risk HPV-type, being present in 87.3% of the cases in single and multiple infections. The five most common high risk HPV types seen in single infections are HPV 16 (31.3%), HPV 18 (19.7%), HPV 35 (5.4%), HPV 31 (1.4%) and HPV 52 (1.4 %). Conclusion: There is high prevalence of HPV-DNA in invasive cervical cancers in this region, with HPV 16, HPV 18, HPV 35, HPV 31, and HPV 52 being the predominant types. HPV vaccination and testing will greatly reduce the burden of cervical cancer in this geographical region.